2015
DOI: 10.4028/www.scientific.net/amr.1087.126
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ultrasonic Treatment on the Oxidation Resistance and Microstructure of Fe<sub>80</sub>Cr<sub>20 </sub>Alloy Powder at High Temperature Oxidation Process

Abstract: Effect of ultrasonic treatment on the oxidation kinetics and microstructure of Fe80Cr20alloy is investigated. The aim of this study is to improve the surface morphology and oxidation resistance of the Fe80Cr20alloy powder as a raw material. Ultrasonic technique is very promise technology and not yet fully explored. The Fe80Cr20material was treated by ultrasonic technique (UT) at various times of 3.5 h, 4.5 h, 5 h and followed by cold compaction with force of 13 Newton. The oxidation test was carried out using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Intermetallic Fe 80 Cr 20 developed by using mechanical alloying with milling time of 40 hours and 60 hours, prior to implanted by using Lanthanum (La), it is consolidated at temperature of 1273 K and pressure of 25 MPa [7]. FeCrAl is treated using ultrasonic technique prior to nickel electroplating which have been studied [8,9] and they found that the ultrasonic technique effective to break the agglomerates or to improve homogeneity, improve surface morphology of the FeCrAl alloys. Some previous research above shows that the crystallite size of Fe80Cr20 alloy, clear correlation with temperature operation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intermetallic Fe 80 Cr 20 developed by using mechanical alloying with milling time of 40 hours and 60 hours, prior to implanted by using Lanthanum (La), it is consolidated at temperature of 1273 K and pressure of 25 MPa [7]. FeCrAl is treated using ultrasonic technique prior to nickel electroplating which have been studied [8,9] and they found that the ultrasonic technique effective to break the agglomerates or to improve homogeneity, improve surface morphology of the FeCrAl alloys. Some previous research above shows that the crystallite size of Fe80Cr20 alloy, clear correlation with temperature operation.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous research above shows that the crystallite size of Fe80Cr20 alloy, clear correlation with temperature operation. Ball milling and ultrasonic technique is shown inconvenience results in growth rate of crystallite size at high temperature operation [3][4][5][6][7][8][9][10][11]. Therefore, this study will combine between ball milling and ultrasonic technique.…”
Section: Introductionmentioning
confidence: 99%